Dos casos de leucismo parcial en el gorrión casero Passer domesticus, en dos localidades del norte de México - Cortinas-Salazar, Jorge Luis; Contreras-Balderas, Armando (Instituto de Ecología, A.C., 2014)
There is limited information on chromatic aberrations in Mexican birds especially in the exotic bird, house sparrow (Passer domesticus). We report two cases from northern Mexico.